THE EFFECTIVENESS OF THROWING AND RACKET DEFENSE TRAINING MODELS ON THE DEFENSE ABILITY OF MEN'S SEPAKTAKRAW ATHLETES - Basyiruddin, Burhan; Wenly, Ayu Purnama; Nasution, Harry Syahputra; Akbar, Muh. Ali (Gladi : Jurnal Ilmu Keolahragaan, 2024)
This research aims to determine the increase in defensive ability with a throwing training model and to determine the increase in defensive ability with a training model using a racket. Used an experimental method with a population of 6 male PPLP sepaktakraw DKI Jakarta athletes. In sampling, a saturated sample technique or (total sampling) is used, that is, all members of the population are used as samples. The results of data analysis are as follows: the defensive training group with throws obtained an average value of 3.67. The standard deviation value of the difference is 0.94, the standard error value of the mean of difference is 0.67 and the calculated t value is 5.50. The defensive training group with a racket got an average score of 8.33. The standard deviation value of divergence is 1.25. The standard error value of the mean of difference is 0.88 and tcount is 9.45, ttable 2.78. These two groups got a standard deviation value from defensive training with a throw of 2.05 and defensive training with a racket of 0.47. The standard error value of the mean difference is 1.22, tcount 3.29, ttable 2.78 with a significance level of α = 5% so that the tcount is greater than the ttable. From the results of the research conducted, it can be concluded using statistical calculations that there is a significant increase in ability after being given throwing defense training and defensive training using a racket.